Copyright in Malaysian creative industry: empowerment or restriction? - Abdul Ghani Azmi, Ida Madieha; Ismail, Suzi Fadhilah; Daud, Mahyuddin; Ali, Adibah; Alavi, Rokiah (Global Academic Excellence (GAE), 2017)
The size and contributions of the creative industry globally including ASEAN countries is now rapidly booming as a result of the digital technologies becoming a convenient medium to broadcast creative works. Originally, copyright is the core that empowers the value of the industry. Nevertheless, there were studies finding that creators did not fully benefit from their own works since the bargaining power in common business models have been manipulated by the investors/companies. There were claims that investors have the upper hand in the negotiation on the proceeds from the works, and not the creators. Copyright here may be a restriction to the society where there will be tendency for creators to be discouraged to produce more creative works since they do not fully enjoy the intended financial benefit from copyright. The aim of this paper is to understand such conflicting interest between the content creators and investors. In doing so, the paper analyses the issue from the perspective of how copyright law works in the creative industry and whether this business model actually empowers or restricts the industry. It concludes with suggestions that may be undertaken by the deprived creators to have more bargaining power in their dealings with investors.